30 nm T-gate enhancement-mode InAlN/AlN/GaN HEMT on SiC substrates for future high power RF applications. (August 2017) - Murugapandiyan, P.; Ravimaran, S.; William, J.
Abstract: The DC and RF performance of 30 nm gate length enhancement mode (E-mode) InAlN/AlN/GaN high electron mobility transistor (HEMT) on SiC substrate with heavily doped source and drain region have been investigated using the Synopsys TCAD tool. The proposed device has the features of a recessed T-gate structure, InGaN back barrier and Al2 O3 passivated device surface. The proposed HEMT exhibits a maximum drain current density of 2.1 A/mm, transconductance g m of 1050 mS/mm, current gain cut-off frequency f t of 350 GHz and power gain cut-off frequency f max of 340 GHz. At room temperature the measured carrier mobility ( μ ), sheet charge carrier density ( n s ) and breakdown voltage are 1580 cm 2 /(V · s), 1.9 × 10 13 cm − 2, and 10.7 V respectively. The superlatives of the proposed HEMTs are bewitching competitor or future sub-millimeter wave high power RF VLSI circuit applications.